2011
DOI: 10.1613/jair.3197
|View full text |Cite
|
Sign up to set email alerts
|

Soft Constraints of Difference and Equality

Abstract: In many combinatorial problems one may need to model the diversity or similarity of sets of assignments. For example, one may wish to maximise or minimise the number of distinct values in a solution. To formulate problems of this type we can use soft variants of the well known AllDifferent and AllEqual constraints. We present a taxonomy of six soft global constraints, generated by combining the two latter ones and the two standard cost functions, which are either maximised or minimised. We characterise the com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…A number of other studies (Petit and Trapp 2015, Trapp and Konrad 2015, Camm 2014, Eiter et al 2013, Hebrard et al 2011, Danna and Woodruff 2009, Schittekat and Sörensen 2009, Hentenryck et al 2009a, Glover et al 2000, Kuo et al 1993 have demonstrated interest in exploration beyond the single solution returned by the solver. These studies discuss generating multiple solutions to combinatorial problems, and some further integrate diversity into their discussions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies (Petit and Trapp 2015, Trapp and Konrad 2015, Camm 2014, Eiter et al 2013, Hebrard et al 2011, Danna and Woodruff 2009, Schittekat and Sörensen 2009, Hentenryck et al 2009a, Glover et al 2000, Kuo et al 1993 have demonstrated interest in exploration beyond the single solution returned by the solver. These studies discuss generating multiple solutions to combinatorial problems, and some further integrate diversity into their discussions.…”
Section: Introductionmentioning
confidence: 99%